THE ROLE OF TEACHERS IN TRANSACTIONAL AND TRANSFORMATIONAL LEARNING - Askar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
The main focus of the research is to describe the main concepts of transactional learning and transformational learning. Research was carried out through literature studies, with data collection using a